CHARACTERISTICS OF KANSAI-BEN ACCENT BY AIKO-SENOU CHARACTERIN ANIME OJAMAJO DOREMI (STUDY OF PHONETIC) - Gabriela M.G Sumampow; Fince Sambeka (SoCul: International Journal of Research in Social Cultural Issues, 2021)
The result of speech is the use of language sounds, occurs in the process of high and low and the strength of the sound of speech. The verbal result of a use a language sound, happens on how high and low, and how weak and strong of the pronunciation of the word, it is what differentiate the meaning of the word or sentence. That is what we usually called “accent”. The main goal of this research is to understand the characteristics of Kansai-ben accent in ojamajo-doremi anime. This research focuses on the Kansai-ben accent spoken by the object of the research which is Aiko-senou in Anime Ojamajo Doremi. Descriptive qualitative method is used to analyze and to describe how Kansai-ben accent was used by Aiko Senou then determining the characteristic based on the result that has been analized through the software speech analizer. The finding shows that there are 4 accent characteristics (used by Aiko-senou in Ojamajo-doremi). Dielect is a an utterance whose background is the domicile of the speaker